Risk Behaviors among Street Adolescents in Urban Bangladesh: A Cross-Sectional Study - Abdullah Al Noman; Md Borhan Uddin; Shaheen Sultana; Irfan Nowroze Noor; Shaheda Hamid; Mohammad Nurunnabi (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Street children, marginalized and vulnerable, face exploitation and risky behaviors due to poverty, neglect and social deprivation. Rapid urbanization has led to a rise in their numbers, particularly in developing countries like Bangladesh. Materials and methods: This cross-sectional study assessed risk behaviors among 260 purposively selected street adolescents aged 10–18 years in Dhaka and Chittagong. Data were collected through pretested, semi-structured interviews from January to December 2017. Results: The majority of street adolescents were aged 13–16 years (76.2%) with a mean age of 14.8±1.6 years. Most were male (81.0%) and had little or no formal education. While 75.8% reported their parents living together, only 36.5% were living with them; many stayed with friends (81.2%) and spent time in public transit areas (60%). Key findings on substance use revealed that 73.8% of respondents used substances, primarily cigarettes (58.2%), ganja (25.6%), and glue (13.3%). Loneliness, mental pressure, and curiosity were significant contributing factors. A notable 12.7% of respondents reported experiencing early sexual harassment, mostly by relatives. Sexual risk behaviors included early sexual encounters (16.2%), with curiosity being the leading cause. Among those with sexual experience, 23.8% had engaged in sex as a profession. Chi-square and logistic regression analyses showed significant associations between substance use and factors such as age, education, family structure, and income (p<0.05). Older adolescents, males, and those not living with parents had higher rates of substance use. Family structure and parental presence played a protective role, with family substance use also influencing children’s behavior. Conclusion: These findings highlight the heightened vulnerability of street adolescentsto substance abuse and sexual exploitation, emphasizing the urgent need for focused interventions that prioritize family support, education and prevention of substance use. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 10-16